2021
DOI: 10.2903/j.efsa.2021.6680
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of animal diseases caused by bacteria resistant to antimicrobials: Dogs and cats

Abstract: In this opinion the antimicrobial‐resistant bacteria responsible for transmissible diseases that constitute a threat to dog and cat health have been assessed. The assessment has been performed following a methodology based on information collected via an extensive literature review and expert judgement. Details of the methodology used for this assessment are explained in a separate opinion. A global state of play of antimicrobial resistant Staphylococcus pseudintermedius , St… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
35
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(35 citation statements)
references
References 31 publications
0
35
0
Order By: Relevance
“…A European multicentre study involving 14 countries and collecting data between 2008 and 2013 also showed that, overall, E. coli was the most frequently identified bacteria in UTI cases from dogs and cats, accounting for 59.5% and 59.3% of all isolates analysed (Marques et al, 2018 ). Information on the proportion of antimicrobial resistance in clinical E. coli from dogs and cats is reported in Table 2 according EFSA AHAW Panel ( 2021a ).…”
Section: Assessmentmentioning
confidence: 99%
See 4 more Smart Citations
“…A European multicentre study involving 14 countries and collecting data between 2008 and 2013 also showed that, overall, E. coli was the most frequently identified bacteria in UTI cases from dogs and cats, accounting for 59.5% and 59.3% of all isolates analysed (Marques et al, 2018 ). Information on the proportion of antimicrobial resistance in clinical E. coli from dogs and cats is reported in Table 2 according EFSA AHAW Panel ( 2021a ).…”
Section: Assessmentmentioning
confidence: 99%
“…Resistance to antibiotics varied tremendously between studies and countries and even within countries. The proportion of resistance reported in individual studies with at least 50 E. coli isolates, sorted by continent, is presented in Figure 1 (EFSA AHAW Panel, 2021a ).…”
Section: Assessmentmentioning
confidence: 99%
See 3 more Smart Citations